Evaluation of selection systems in alternate and in situ environments in wheat Triticum aestivum L. - Campuzano D., Luis Fernando; Molina G., José; Rajaram, Sanjaya (Revista de Ciencias Agrícolas, 2015)
Wheat breeding by alternating locations, known as Shuttle Breeding, has been the most efficient way to introduce and select genes for rust resistance, photoperiod insensitivity, and dwarfism, which are important attributes for increased yield. After 35 years of its implementation in Mexico and elsewhere in the world, this work was aimed to evaluated the benefits of the alternating system and determined which system, between alternating systems (Toluca-Cd. Obregon, Ciudad Obregon-Batán Batán -Toluca) and in situ systems (Toluca Toluca, Cd. Obregon-Cd. Obregon-Batán Batán), provides the largest number of wheat lines with high yield and stability. As well as the association with the specific or general adaptation. The genetic material was gathered from six wheat crosses and, after the modified mass selection, 32 lines were selected for each system to be evaluated on a14 x 14 alpha-lattice design, in an agricultural cycle, in three selection environments, in Cuidad Obregón, Batán, and Toluca, Mexico. The results showed that alternate selection compared to in situ site selection exhibited a 2.2% increase in yield. BT was the best system since it showed the highest yield and greatest number of lines with high performance and stability. In contrast, BY, TT, and YY systems made the lowest contribution to the lines with highly yield and stability.